Overview of the Utilization of Palm Empty Fruit Bunch (PEFB) as Raw Material for Bioplastic Production - Pakpahan, Cindy; Utarina, Leila; Cahyani, Aulia; Moulita, R.A. Nurul; Wulandari, Daya (International Journal of Research in Vocational Studies (IJRVOCAS), 2025)
This research examines the utilization of Palm Empty Fruit Bunch (PEFB), a byproduct of the palm oil sector, as a sustainable feedstock for bioplastic manufacturing. Bioplastics, derived from natural substances like cellulose, starch, and vegetable oils, offer a sustainable substitute for traditional petroleum-based plastics, which substantially contribute to environmental degradation. This research examines the processes of cellulose extraction, delignification, and the diverse pre-treatment techniques employed to transform PEFB into bioplastics. The findings indicate that PEFB is abundant in cellulose, rendering it a viable material for bioplastic manufacturing. Moreover, the inclusion of plasticizers such glycerol and chitosan enhance mechanical qualities, including tensile strength and flexibility, while preserving biodegradability. The study also emphasizes the influence of various processing conditions and additives on the ultimate attributes of the bioplastic, such as water resistance and mechanical performance. The results indicate that bioplastics sourced from PEFB may aid in diminishing plastic waste and fostering sustainable materials in sectors like packaging. The analysis continues by underscoring the necessity for more research to enhance production techniques and evaluate the scalability of PEFB-based bioplastics in practical applications.